2017
DOI: 10.4081/audiores.2017.187
|View full text |Cite
|
Sign up to set email alerts
|

Day-Case Management of Chronic Suppurative Otitis Media with Cholesteatoma with Canal Wall down Technique Surgery: Long-Term Follow-up

Abstract: The overall number of day-case otologic surgery cases is increasing; however, there is limited experience about performing canal wall down tympanoplasty in patients with chronic suppurative otitis media with cholesteatoma in this setting. The objective of this study was to assess the success of this technique as daycase surgery in terms of results and complications over an 8-year follow up period. We included in this study 42 patients undergoing canal wall down technique tympanoplasty surgery for chronic suppu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…1). After selection based on title and abstract, and subsequent full-text screening, 35 articles discussing 34 studies were considered eligible for further review (2–5,11–41). Cross-reference checking revealed no additional relevant articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). After selection based on title and abstract, and subsequent full-text screening, 35 articles discussing 34 studies were considered eligible for further review (2–5,11–41). Cross-reference checking revealed no additional relevant articles.…”
Section: Resultsmentioning
confidence: 99%
“…The latter speculation is supported when looking at the most frequent reasons for admission: PONV (27%) and late-scheduled surgery (8%). Five studies (5,17,24,28,30) described the presence of an underlying infectious or destructive disease and the effect on PONV, length of surgery and hospital stay. In the study population of Hasan et al (17), 58% had a cholesteatoma whereby the presence thereof was associated with a higher risk of PONV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 Ralli G et al concluded that with proper preoperative selection of the patients, mastoidectomy with tympanoplasty can be carried out in a day surgery setting with no significant effects on effectiveness of surgery and post-operative symptoms. 9 Data was entered, studied and analyzed with SPSS version 19. Frequencies, relationship and proportions were generated.…”
Section: Discussionmentioning
confidence: 99%